Partial duplication of the anterior communicating artery: A case report - Hideki Endo, MD, PhD; Hidetoshi Ono, MD; Toshiichi Watanabe, MD; Hirohiko Nakamura, MD, PhD (Radiology Case Reports)
Anatomical variations in the anterior cerebral artery and/or anterior communicating artery complex are common. However, partial duplication is a rare variant of the anterior communicating artery. To the best of our knowledge, there are only a few reports describing a partially duplicated anterior communicating artery. We report a case of a partially duplicated anterior communicating artery associated with an intracranial aneurysm, which was diagnosed by 3-Tesla magnetic resonance angiography and digital subtraction angiography. A 43-year-old woman was admitted to our hospital for postoperative examinations following coil embolization of an unruptured right internal carotid artery aneurysm performed 1 year earlier. Magnetic resonance angiography and digital subtraction angiography revealed no recurrence of the treated aneurysm, and a partially duplicated anterior communicating artery—there were 2 separate anterior communicating arteries on the right side and one on the left side. Digital subtraction angiography under contralateral carotid artery compression showed no aneurysm in the anterior communicating artery complex. This report provides additional evidence of partially duplicated anterior communicating arteries associated with an intracranial aneurysm. Careful imaging assessment is important to identify this rare anatomical variant, as well as other concomitant variations and associated aneurysms.